American picture palaces the architecture of fantasy - Naylor, David (Van Nostrand Reinhold, 1981)
The history of American movie theaters focusing on the larger, more ornate ones exploring both their facades and their interiors and emphasizing their ultimate fate.
Keywords: Geschichte; Bioscopen; Cinémas - États-Unis; Motion picture theaters -- United States; Kino; USA